Coupling analysis of multi-systems urbanization: Evidence from China - Junqiang Luo; Weijing Ma; Shuang An; Zining Zhang; Yanchuan Fu; Hejun Huang; Genying Chang (Ecological Indicators)
China’s urbanization rate has reached 66.16 %, indicating its transition to a more complex mid-to-late stage, which makes multi-systems research on urbanization essential. However, studies on urbanization from multiple perspectives are still limited, hindering a full understanding of its multifaceted nature. This study focuses for the first time on 295 prefecture-level cities and above in China from 2000 to 2020, developing an evaluation system for multi-systems urbanization to assess coupling and coordination. Utilizing methods such as the entropy method, coupling coordination model, Theil index, and Geodetector, this study explores the spatiotemporal differentiation and driving factors of urbanization coupling coordination. The results indicate: (1) The coupling coordination degree of urbanization shows a steady upward trend. Highly coordinated cities are primarily distributed in the core city’s radiation circles, coastal economic belts, provincial capitals in the central and western regions, and northern industrial city zones. Low-coordination cities are mainly found in the Qinghai-Tibet Plateau, Yunnan-Guizhou Plateau, the border areas of Gansu, Shaanxi, Sichuan, Chongqing, and Hubei, the Hetao area of the Yellow River Basin, the agricultural regions of the Huanghuaihai Plain, and the southeastern hilly and mountainous areas. (2) The degree of uneven urbanization development initially expands and then contracts, with intra-regional imbalances following the pattern: “Eastern Coastal Area > Northeast Area > Middle Reaches of the Yangtze River Area > Northern Coastal Area > Middle Reaches of the Yellow River Area > Southwest Area > Southern Coastal Area > Northwest Area.” (3) The coupling and coordinated development of urbanization is closely related to the economic foundation and production energy usage. This study provides decision-making support for promoting the multi-systems coupling and coordinated development of urbanization in China, as well as in other developing nations and globally.